The use of Sand Filter - Activated Carbon in the Treatment Effluents of Al-Kasak Refinery in Mosul - AI-Hashimi, Zena Fakhri (Basrah Journal for Engineering Sciences, 2010)
The study focuses on using sand and activated carbon filters for treating of A l-Kasak refinery wastewater. The wastewater contains many contaminants and organic and chemical materials. Many tests were performed such as pH, E.C, T.S, COD, BOD, Phenole, Oil, and NH3, after and before treatment with a filter in order to determine effluent characteristics. The highest T.S removal efficiency with sand filter was 93% and 90% for oil. The highest removal efficiency with activated carbon filter happened to Phenol, which was 99%, and for COD and BOD was(81- 90) % and (77-9 1)% continuously. The study shows that the cycle time of 9 hr gives the best removal efficiency for organic wastewater, especially for high organic load. It was recommended to use a sand-activated carbon filter to treat refinery wastewater because the effluents were within the Limits of refinery waste water casting and river casting.